PHYTOAVAILABILITY OF THE CADMIUM, LEAD AND CHROMIUM IN SOYBEAN CULTIVATED IN ARGISSOLO VERMELHO EUTRÓFICO, TREATED WITH COMMERCIAL FERTILIZERS - GONÇALVES Jr., Affonso Celso; PESSOA, Antônio Carlos dos Santos (Scientia Agraria, 2002)
The aim of this work was to evaluate the availability of the toxic heavy metals: cadmium, lead and chromium, in soybean, from some fertilizers. Five fertilizers and soluble salts contend Cd, Pb and Cr were used. All the treatments were accomplished in vases of 2,5 L with application of two doses, 50 and 100 kg ha- 1 for the fertilizers and 25 and 50 kg ha-1 for the salts. The vegetable tissue of soybean was submitted to the analysis of Cd, Pb and Cr, by atomic absorption spectrometry (flame). In the plants cultivated in the soil Pve, the largest release of the metals occurred in the following treatments: for the Cd, CdCl2.H2O 2, FTE Cerrado 2, Stimussed Plus and FTE Cerrado 1; for Pb, Zincogran 2, Micronutri 121 2 and 1, (CH3COO)2Pb.3H2O 2 and FTE Cerrado 2 and for Cr, CrCl3.6H2O 2 and 1 and Zincogran 2 and 1. The increase of the dosage of the applications of the fertilizers and of the salts contentaining the toxic heavy metals favored the increase of the concentration of the metals in the plants.